Cyclic uniaxial mechano optical studies on stress-softening behavior of natural rubber/clay nanocomposites. (15th April 2019) - Liang, Yurong; Tan, Yingjie; Guo, Yuanhao; Hao, Mingzheng; Zhang, Tao; Wang, LinYan; Mutlu, Zeynep; Cakmak, Miko
Abstract: A real-time spectral birefringence technique was implemented to follow the coupled relationships between birefringence, true stress and true strain of natural rubber (NR)/organo-modified clay (OC) nanocomposites (NRCNs) during cyclic stretching and retraction. The dynamics of structural evolution was also followed by off-line Wide Angle X-ray Diffraction. The results show that the birefringence and true stress at the same level of strain increases with the OC content during stretching. During the strain retraction, the birefringence of NRCNs with low OC content initially decreases slower when plotted against true strain and then decreases faster as the strain is retracted further. In contrast, the NRCNs with higher OC content exhibit a lower birefringence than the value during stretching due to more rupture of rubber-filler bonding occurred during stretching. The birefringence-true stress retraction curves show that the birefringence of NRCNs with low OC concentrations increases slightly which is caused by the further formation of rubber crystallites at high strain when optimum amount of filler is present, then the birefringence declines slowly due to the relaxation of rubber chains. While the NRCNs with higher OC content have a rapid stress decrease with a small strain retraction (limited chain relaxation), thus they exhibit a birefringence plateau during the initial stress retraction and a sharp decline as the stress decreases further. Graphical abstract: Image 10598 Highlights: The strain hardening, strain induced crystallization during stretching and Mullins effect become more pronounced as the clay content increases. Birefringence-true strain curve exhibit a crossover behavior in NRCNs with low OC content. Higher OC content causes NRCN's to exhibit higher crystalline chain orientation.